Biking in the land of the car - clashes of mobility cultures in the USA - Jensen, Ole B. (Proceedings from the Annual Transport Conference at Aalborg University, 2007)
This paper is theoretical in its attempt to articulate and theorize the notion of ‘mobility culture’. It is empirical in its choice of cases illustrating the notion of mobility culture. The paper explores three cases in the USA; The East Coast Greenway bicycle corridor and the contemporary tensions and conflicts over bikes on Manhattan, NYC. The latter case is particularly scoped in relation to the ‘critical mass’ event and the NGO ‘Transportation Alternatives’. Based upon the theoretical framing and empirical field studies conducted in the US the paper put forwards an illustration of how to comprehend urban mobility cultures and the power-ridden conflicts that arises when these clash. By looking into North American cases the paper brings a comparative dimension to the European taken-for-granted status of urban cyclists. Furthermore, the paper aims to show that there is more than urban logistics of transportation flows at stake when mobility cultures clashes. The clashes of urban mobility cultures make us see that infrastructures and urban transportation is about more that instrumental movement of people from point A to point B. What are at stake are also notions of community, social identities and culture.